Association of Sedentariness and Health Promoting Lifestyles in Older Adults [Actividad Física y Perfil de Estilos de Vida Promotores de la Salud en Adultos Mayores Chilenos] - Herrera-Valenzuela, T (Sociedad Medica de Santiago, 2017)
Background: Part of having healthy lifestyles should be a regular practice of physical activities. Aim: To evaluate the association between the practice of physical activity and healthy lifestyles in older people. Material and Methods: The Health-Promoting Lifestyle Profile survey was applied to 1688 older people living in the community, aged 72 ± 7 years (61% women). This survey includes questions about regular physical activity. Results: Twenty four percent of surveyed participants declared to practice physical activities at least three times per week, without gender differences. Sedentariness increased along with age. There was a negative association between low physical activity and healthy lifestyles (odds ratio (OR): 3.2 confidence intervals (CI): 2.3-4.5). There was also an association between sedentariness and low self-realization (OR 2.4 CI: 1.8-3.3), low responsibility with health (OR 1.6 CI: 1.2-2.1), low concern about nutrition (OR 1.8 CI: 1.4-2.4), low stress management (OR 2.0 CI: 1.5-2.7) and low interpersonal support (OR 2.0 CI: 1.5-2.6). Conclusions: Sedentariness is negatively associated with health promoting lifestyles in this group of older people. © 2017, Sociedad Medica de Santiago. All rights reserved.